TRATAMENTOS DE FRATURAS DO RÁDIO E DA ULNA EM CÃES E GATOS: REVISÃO - COSTA, R. C.; SCHOSSLER, J. E. W. (Archives of Veterinary Science, 2002)
Os métodos de tratamento das fraturas do rádio e da ulna são revisados. São descritos e avaliados o tratamento conservador e as técnicas de banda de tensão, fixação externa, pinos intramedulares, placas e parafusos nos diferentes tipos de fratura envolvendo desde a porção proximal à distal do rádio e da ulna. Fractures treatments of the radius and ulna in dogs and cats: A review Abstract A review of the treatments of radius and ulna fractures in dogs and cats was carried out. The conservative therapeutics as well as the surgical techniques as tension band, external fixation, intramedular pins and bone plate are described and comparatively evaluated in regard to the differente types of fractures from the proximal up to the distal portions of both the radius and the ulna.